MODIFICATION OF SILVER NANOWIRE COATINGS WITH INTENSE PULSED ION BEAM FOR TRANSPARENT HEATERS - Kaikanov, Marat; Amanzhulov, Bauyrzhan; Demeuova, Gulzat; Akhtanova, Gulnur; Bozheyev, Farabi; Kemelbay, Aidar; Tikhonov, Alexander (MDPI, 2020)
: In this report, an improvement of the electrical performance and stability of a silver nanowire (AgNW) transparent conductive coating (TCC) is presented. The TCC stability against oxidation is achieved by coating the AgNWs with a polyvinyl alcohol (PVA) layer. As a result, a UV/ozone treatment has not affected the morphology of the AgNWs network and the PVA protection layer, unlike non-passivated TCC, which showed severe degradation. The irradiation with an intense pulsed ion beam (IPIB) of 200 ns duration and a current density of 30 A/cm2 is used to increase the conductivity of the AgNWs network without degradation of the temperature-resistant PVA coating and decrease in the TCC transparency. Simulations have shown that, although the sample temperature reaches high values, the ultra-high heating and cooling rates, together with local annealing, enable the delicate thermal processing. The developed coatings and irradiation strategies are used to prepare and enhance the performance of AgNW-based transparent heaters. A single irradiation pulse increases the operating temperature of the transparent heater from 92 to 160 ◦C at a technologically relevant voltage of 12 V. The proposed technique shows a great promise in super-fast, low-temperature annealing of devices with temperature-sensitive components.
Keywords: silver nanowires; transparent heater; intense pulsed ion beam; protective layer; Research Subject Categories::NATURAL SCIENCES::Physics